Simulation of magnetic induction distribution in a coaxial linear motor with axial and radial direction of permanent magnets magnetization - G.M. Golenkov (National Technical University "Kharkiv Polytechnic Institute", 2014)
The paper presents results of computer simulation and experimental study of magnetic induction distribution in a coaxial linear motor air gap throughout the length of the runner active part at different heights of the air gap between the runner and the inductor magnetic core for motors with axial and radial direction of the permanent magnets magnetization.